The Equality of Parties in Sale-and-Purchase Binding Agreement on Land and Building with the Pre-Project Selling System - Cokorda Gede Swetasoma (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2021)
The study aims to analyze the legal implications of the Regulation of the Minister of Public Works and Housing of the Republic of Indonesia Number 11/PRT/M/2019 on the Sale-and-Purchase Binding Agreement on Land and Building. The emphasis lies on the equality of parties that involve in buying and selling property using pre-project selling system. This study used legal materials and concepts to approach the issue. The primary legal materials consisted of statutory regulations; and the secondary legal materials consisted of books, scientific journals, and electronic articles. The Regulation of the Minister of Public Works and Housing of the Republic of Indonesia Number 11/PRT/M/2019 does not regulate sanctions for buyer’s unilateral cancellation. According to the Regulation, if buyer unilaterally cancels transaction, seller (housing developer) receives only ten percent of the sum of money that the buyer has paid. This provision does not fulfil the principle of equality for the parties. The objectives of law (legal justice, benefits, and certainty) cannot be achieved because of the inequality of parties. The condition leads to seller’s loss. It is especially happened if house that has been partially built-in accordance to special conditions at the request of the buyer. The house can be difficult to be sold.DOI: https://doi.org/10.22304/pjih.v8n3.a7